Data analytics and management in data intensive domains : XIX International Conference, DAMDID/RCDL 2017, Moscow, Russia, October 10-13, 2017, Revised selected papers /: XIX International Conference, DAMDID/RCDL 2017, Moscow, Russia, October 10-13, 2017, Revised selected papers. (2018) - Unknown
No abstract available